TEACHING PRONUNCIATION WITH THE HELP OF MODERN TECHNOLOGY - Dagarov Sodiq Murtoza o‘g‘li,; Mamasidiqov Muhammadjon Saidmurod o’g’li,; Maxramov Ozodbek Shavkat o’g’li, (TADQIQOTLAR, 2026)
Annotation This article explores the role of modern technology in teaching pronunciation in language learning. It emphasizes that correct pronunciation is essential for effective communication  and  helps  learners  speak  more  clearly  and  confidently.  The  article examines various technological tools such as mobile applications, speech recognition software, online videos, and virtual learning platforms. These tools allow students to listen  to  native  speakers,  practice  pronunciation  repeatedly,  and  receive  immediate feedback  on  their  performance.  Furthermore,  the  article  discusses  how  technology creates an interactive and flexible learning environment. It also highlights the important role of teachers in guiding students and supporting the effective use of technology. In conclusion,  modern  technology  makes  pronunciation  learning  more  engaging, accessible, and efficient.